REIMAGINING FUTURE RELATIONS BETWEEN INTERNATIONAL AND NATIONAL LAW WITH SPECIAL REFERENCE TO THE PALESTINIAN SITUATION (Journal of International Studies, 2023)
This paper examines the issue of the relationship between international and national law that leads to the gradation of laws. Is international law superior or inferior to national law? This question pushed the existing theoretical positions to find more convincing answers and practical solutions to this question. The article differentiates between two doctrines, the first is monism between international and national law, and the second is the dualism between international and national law. The status of international law in the national legal system is determined by the national constitution of each country. The article discusses a crucial issue associated with a substantial principle on which international law is based: the principle of state sovereignty and the critical relationship between international law and national law. The article aims to clarify the nature of the relationship with a specific reference to the experiences and challenges faced by the State of Palestine. To achieve the objectives of the article, doctrinal legal research methodology was adopted. Accordingly, this study concluded that there are two conflicting doctrines in determining the status of international law in the national legal system. Since the establishment of the State of Palestine and being a non-member observer state at the United Nations, the Palestinian legislature has adopted the doctrine of monism. The study would assist the international community in understanding the legal nature of the Palestinian constitutional system and its position related to the value of treaties in Palestine. The study emphasises the need to harmonise Palestinian legislation in order to be in line with international treaties.